PENGARUH MOTIVASI DAN MENTAL WIRAUSAHA TERHADAP JIWA WIRAUSAHA MUDA - Eni Duwita Sigalingging; Fiderlin Buulolo (PARETO : Jurnal Riset Bisnis dan Manajemen, 2025)
This study aims to determine the effect of Motivation and Entrepreneurial Mentality on Young Entrepreneurial Spirit (Case Study of Students From the Faculty of Economics and Business at the University of Nias with an Interest In Entrepreneurship). The results of this study indicate that motivation and entrepreneurial mentality affect the entrepreneurial spirit. Furthermore, in this study, multiple linear regression equations were obtained using primary data in the form of a questionnaire about motivation, entrepreneurial mentality and young entrepreneurial spirit. The questionnaire was tested for validity and reliability before processing research data. The test tool used is the classical assumption test. The results showed that partially the motivation ) (1,832) > and entrepreneurial mentality ) (8,424) > (1,697) so that it positive and significant to the young entrepreneurial spirit (Y) at α = 0.05. Meanwhile, simultaneously the motivational and entrepreneurial mental variables have a positive and significant effect on the entrepreneurial spirit with (35,522) > (3,316) at α = 0,05.